2022
DOI: 10.1186/s12870-021-03414-7
|View full text |Cite
|
Sign up to set email alerts
|

Physiological mechanism of strigolactone enhancing tolerance to low light stress in cucumber seedlings

Abstract: Strigolactone is a newly discovered type of plant hormone that has multiple roles in modulating plant responses to abiotic stress. Herein, we aimed to investigate the effects of exogenous GR24 (a synthetic analogue of strigolactone) on plant growth, photosynthetic characteristics, carbohydrate levels, endogenous strigolactone content and antioxidant metabolism in cucumber seedlings under low light stress. The results showed that the application of 10 μM GR24 can increase the photosynthetic efficiency and plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…In addition, GR24 increased nitric acid (NO) in the Cd-sensitive genotype, which was associated with modulation of the NO signaling pathway, increased SOD and POD activities, augmented AsA and GSH levels, and improved the activity of ascorbate-glutathione cycle enzymes, including APX, GPX, GR, DHAR, and MDHAR ( Qiu et al, 2021 ). Likewise, 10 μM GR24 enhanced the accumulation of carbohydrates and the synthesis of sucrose-related enzyme activities, increased the photosynthetic efficiency and plant biomass, antioxidant enzyme activities, and antioxidant substance contents, and reduced H 2 O 2 and MDA levels in cucumber ( Cucumis sativus ) seedlings under low light stress ( Zhou et al, 2022 ). Similarly, exogenous SL relieved oxidative damage and photosynthetic inhibition of cucumber seedlings under salt stress through the MAPK cascade pathway ( Zhang et al, 2022 ).…”
Section: Interplay Of Plant Hormones In Conferring Abiotic-induced Ox...mentioning
confidence: 99%
“…In addition, GR24 increased nitric acid (NO) in the Cd-sensitive genotype, which was associated with modulation of the NO signaling pathway, increased SOD and POD activities, augmented AsA and GSH levels, and improved the activity of ascorbate-glutathione cycle enzymes, including APX, GPX, GR, DHAR, and MDHAR ( Qiu et al, 2021 ). Likewise, 10 μM GR24 enhanced the accumulation of carbohydrates and the synthesis of sucrose-related enzyme activities, increased the photosynthetic efficiency and plant biomass, antioxidant enzyme activities, and antioxidant substance contents, and reduced H 2 O 2 and MDA levels in cucumber ( Cucumis sativus ) seedlings under low light stress ( Zhou et al, 2022 ). Similarly, exogenous SL relieved oxidative damage and photosynthetic inhibition of cucumber seedlings under salt stress through the MAPK cascade pathway ( Zhang et al, 2022 ).…”
Section: Interplay Of Plant Hormones In Conferring Abiotic-induced Ox...mentioning
confidence: 99%
“…Membrane lipid peroxidation is the major cause of oxidative damage in plants exposed to abiotic stresses [ 37 ]. Specifically, LL stress primarily causes the generation of ROS, such as O 2 ∙ − and H 2 O 2 , which consequently induces a lipid peroxidation and membrane permeability increase, and ultimately triggers the occurrence of oxidative stress [ 38 , 39 ]. In our present study, the level of ROS is remarkably increased when plants are exposed to LL stress, but exogenous PBZ application attenuates this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, T1 and T2 had the most significant enhancement effect, whereas T4 had an insignificant alleviation effect, indicating that the low concentration of SL could alleviate the inhibitory effect of drought stress on P. purpureum , and enhance its photosynthesis capacity. This finding may be due to the fact that SL can regulate the binding of Chl to membrane proteins and thus maintain the stability of chloroplast cyst-like membranes, thereby enhancing the plant’s ability to use light energy to overcome photosystem damage and the photosynthesis performance of the plant [ 17 ]. Sedaghat et al [ 46 ] obtained similar findings in their study on the effect of SL on wheat ( Triticum aestivum L.) under drought stress, in which SL application enhances the net Pn, Gs, and Tr of wheat.…”
Section: Discussionmentioning
confidence: 99%
“…SLs further reportedly inhibit plant branching, control shape root morphology, enhance primary root cell growth to inhibit adventitious root development and growth, and regulate plant secondary growth [ 12 , 13 ]. They are also associated with drought resistance, cold tolerance, salt tolerance and other stress tolerance [ 14 17 ], and photomorphogenesis [ 18 ] and serve as positive regulators of plant responses to certain abiotic stresses [ 19 ]. Sattar et al [ 20 ] applied SL to maize ( Zea mays L.) under drought stress and found that SL improves the water relationship of maize seedlings, increases photosynthesis pigments and gas-exchange parameters, and improves antioxidant enzyme activity.…”
Section: Introductionmentioning
confidence: 99%